Are you in or are you out? Investigating the factors affecting students’ immersion in a location-based AR game for IBSE. - Kyza, Eleni A.; Georgiou, Yiannis (My University, 2014)
It is argued that augmented reality games can promote immersion and feelings of presence, which could support students’ engagement with the learning process. Sustaining presence is crucial but challenging, since immersion is a transient state. As part of a broader design-based research, in this study, we employed a focus group methodology to investigate the perceptions of eighteen 11th graders regarding the factors which affected their immersion during an augmented reality game for inquiry-based science learning.
Keywords: Augmented Reality Games; Learning Process; Students